Cloud Server-based Questionnaire System for Cultural Services in Blue-green Spaces - Fan, Guoqing; Wang, Yu; Zhao, Shengnan; Qiao, Xuning; Qi, Xiudong (International Journal of Natural Resources and Environmental Studies, 2024)
Parks are important carriers of urban blue-green space and cultural services, which are vital to beautify the city and improve the quality of life of residents. Constructing a questionnaire system for cultural services in blue-green spaces is of great significance for evaluating and studying the supply of regional cultural services and quantifying residents’ cultural needs. In this paper, we take Zhengzhou city park as the evaluation object, and based on AliCloud server ECS and WebGIS technology, combined with drone orthophoto and real-life three-dimensional model, we make the questionnaire survey system of blue-green space cultural service to collect residents’ social value preference and suggestions for the park. Respondents enter the system through any device with internet access, browse park pictures and profiles, and participate in the online questionnaire survey, and the collected data on residents’ value preferences can be used to assess the value of the park’s cultural services by methods such as the SolVES model. The system solves the shortcomings such as heavy workload and low response rate of distributing questionnaires in the field. The system integrates a variety of digital technologies and improves the questionnaire survey method, which can effectively improve the efficiency and quality of the questionnaire survey and analyze the problems and deficiencies of the park with the opinions of the respondents, so as to provide the management with references for optimization and standardization, and to promote the enhancement of the quality of cultural services.